CORRELATION BETWEEN STUDENTS' EDUCATIONAL BACKGROUND AND MOTIVATION WITH LEARNING OUTCOMES IN ARABIC LANGUAGE CLASS X AT ISLAMIC INTERNATIONAL BOARDING SCHOOL (IIBS) AL-MAAHIRA - Suria Anisah; Munirul Abidin (Kitaba, 2024)
Arabic language learning is only applied in a few schools and its application experiences several obstacles due to lack of interest. However, if Arabic language learning is applied from the beginning, student interest in learning will increase and will affect student learning outcomes. The purpose of this study is (1) to examine the correlation or relationship between educational background and Arabic learning outcomes (2) to examine the correlation between students' learning interest and Arabic learning outcomes (3) to examine the correlation between students' educational background and students' learning motivation on students' learning outcomes. The subjects in this study were 12 students of class X IIBS Al-Maahira. the data collection technique was to distribute questionnaires related to students' educational background and learning motivation. Data related to student learning outcomes using Arabic midterm exam scores. The data analysis technique is simple correlation analysis. The results of this study are (1) there is a relationship between educational background and learning outcomes as much as 0.710 (2) a simple correlation between learning motivation and correlation results with results as much as 0.710 (3) there is a high and significant relationship between students' educational background and student learning motivation with Arabic learning outcomes by showing a correlation coefficient of 0.736 and a coefficient of determination of 0.541